Factors that contribute to work stress among employees in IOI Loders Croklaan Oils Sdn Bhd / Siti Nurafiqah Rahmat and Nashazieda Azhari - Rahmat, Siti Nurafiqah; Azhari, Nashazieda (2013)
This research paper will study about the factors that contribute to work stress among employees in IOI Loders Croklaan Oils Sdn Bhd. The objective of this study is to examine the relationship between workload, interpersonal relationship at work and work stress. The other objective is to identify the factor that mostly contributes to work stress. In this study the researchers used secondary and primary data in collecting the necessary data. The data of this study was collected by using questionnaires that distributed randomly among the employees in IOI Loders Croklaan Oils Sdn Bhd. The data is analyzed by using Statistical Package for the Social Sciences (SPSS) version 20. A factor analysis was done for the purpose of determining the construct validity of the questionnaire and the independent and dependent variables used in this research. Overall, this research support all the theory made by the previous researchers.